Anthropogenic impact on the historical phytoplankton community of Lake Constance reconstructed by multimarker analysis of sediment‐core environmental DNA. Issue 13 (5th November 2020) - Ibrahim, Anan; Capo, Eric; Wessels, Martin; Martin, Isabel; Meyer, Axel; Schleheck, David; Epp, Laura S.
Abstract: During the 20th century, many lakes in the Northern Hemisphere were affected by increasing human population and urbanization along their shorelines and catchment, resulting in aquatic eutrophication. Ecosystem monitoring commenced only after the changes became apparent, precluding any examination of timing and dynamics of initial community change in the past and comparison of pre‐ and postimpact communities. Peri‐Alpine Lake Constance (Germany) underwent a mid‐century period of eutrophication followed by re‐oligotrophication since the 1980s and is now experiencing warm temperatures. We extended the period for which monitoring data of indicator organisms exist by analysing historical environmental DNA (eDNA) from a sediment core dating back some 110 years. Using three metabarcoding markers—for microbial eukaryotes, diatoms and cyanobacteria—we revealed two major breakpoints of community change, in the 1930s and the mid‐1990s. In our core, the latest response was exhibited by diatoms, which are classically used as palaeo‐bioindicators for the trophic state of lakes. Following re‐oligotrophication, overall diversity values reverted to similar ones of the early 20th century, but multivariate analysis indicated that the present community is substantially dissimilar. Community changes of all three groups were strongly correlated to phosphorus concentration changes, whereas significant relationships to temperature were only observed when we did not account for temporal autocorrelation. Our results indicate that each microbial group analysed exhibited a unique response, highlighting the particular strength of multimarker analysis of eDNA, which is not limited to organisms with visible remains and can therefore discover yet unknown responses and abiotic–biotic relationships.